THE EFFICIENCY OF SURGICAL TREATMENT AND REHABILITATION IN THE RECOVERY OF PATIENTS WITH A CETABULAR POSTERIOR WALL FRACTURES - Ankin, Mykola; Ladyka, Viktoriia; Glynyana, Oksana; Barylovych, Mykola (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Fractures of the posterior wall of the acetabulum are one of the most difficult injuries to treat in Orthopedics and traumatology. The most common causes of this fracture are road traffic accidents, falls from heights, and injuries resulting from military actions. There is a high risk of post-traumatic arthritis at later stages and avascular necrosis, often leading to future disability. Objective. to assess the efficiency of surgical treatment and rehabilitation in patients with acetabular posterior wall fracture. Methods. The study was conducted at the Kyiv Regional Clinical Hospital and Kyiv City Clinical Hospital No. 8 from 2021 to 2023. A total of 44 patients aged 19 to 68 participated in the study. Treatment outcomes and rehabilitation measures were assessed using the Matta and Harris Hip Score scales. All patients underwent open reduction and internal fixation of the posterior wall of the acetabulum with plates and screws. The Kocher-Langenbeck surgical approach was used in all cases. Clinical and radiological results were analyzed at 3, 6, and 12 months in all patients. Results. The Harris Hip Score in the main group was (81.51 ± 4.03) points at 6 months and (87.09 ± 5.31) points at 12 months. In the control group, the scores were (75.43 ± 4.45) at 6 months and (84.01 ± 4.17) at 12 months (p < 0.01). Conclusions. Early closed reduction of hip joint dislocation and surgery with reconstruction of normal joint anatomy and stable fracture fixation is crucial for efficiency of surgical treatment.